2021
DOI: 10.1186/s40560-021-00581-5
|View full text |Cite
|
Sign up to set email alerts
|

Paradox of trimethylamine-N-oxide, the impact of malnutrition on microbiota-derived metabolites and septic patients

Abstract: Background Trimethylamine N-oxide (TMAO) is a microbiota-derived metabolite, which is linked to vascular inflammation and atherosclerosis in cardiovascular (CV) diseases. But its effect in infectious diseases remains unclear. We conducted a single-center prospective study to investigate association of TMAO with in-hospital mortality in septic patients admitted to an intensive care unit (ICU). Methods Totally 95 septic, mechanically ventilated patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…The level of TMAO was low on D7, likely due to low food intake. 59 In contrast, the TMAO levels were significantly elevated on D14. Given that the serum TMAO concentration is associated with many diseases ranging from inflammatory diseases (e.g., pneumonia) to metabolic and cardiovascular diseases, 28 , 60 one can reasonably expect an elevated TMAO level can have negative consequences in IAV-infected hosts.…”
Section: Discussionmentioning
confidence: 91%
“…The level of TMAO was low on D7, likely due to low food intake. 59 In contrast, the TMAO levels were significantly elevated on D14. Given that the serum TMAO concentration is associated with many diseases ranging from inflammatory diseases (e.g., pneumonia) to metabolic and cardiovascular diseases, 28 , 60 one can reasonably expect an elevated TMAO level can have negative consequences in IAV-infected hosts.…”
Section: Discussionmentioning
confidence: 91%
“…Уровень ТМАО в плазме не был связан с классическими сердечнососудистыми факторами риска и с эндотелиальной функцией в здоровой когорте [30]. Концентрация ТМАО в плазме обратно пропорциональна смертности среди тяжелобольных септических пациентов без ССЗ, что можно охарактеризовать как парадокс ТМАО [40]. Положительные эффекты ТМАО зависят от контекста, например, в условиях стресса в моделях переедания ТМАО может проявлять антиоксидантные и противовоспалительные эффекты, наблюдаемые на тканевом уровне, особенно в гепатоцитах, адипоцитах, мышечной ткани и β-клетках поджелудочной железы, а также влияние ТМАО на толерантность к глюкозе различается между здоровыми условиями и патогенными состояниями [28].…”
Section: потенциальное значение тмао в патогенезе атеросклероза: за и...unclassified
“… 80 Another investigation examining 95 patients with sepsis revealed that the impact of malnutrition reflected by plasma TMAO levels in these patients was far more significant than TMAO's proinflammatory effects. 84 Taken together, reducing choline intake rather than eliminating it is beneficial to patients with cardiovascular disease to some extent.…”
Section: Regulating Tmao Levels To Mitigate Coronary Artery Diseasementioning
confidence: 99%